2021
DOI: 10.1097/oi9.0000000000000140
|View full text |Cite
|
Sign up to set email alerts
|

CT scans better assess lateral wall morphology of “stable appearing” intertrochanteric (IT) femur fractures and predict early failure of sliding hip screw (SHS) fixation

Abstract: Objectives: To compare the efficacy of plain x-ray images and computed tomography (CT) to assess the morphology of the lateral wall (LW) component of intertrochanteric (IT) femur fractures and determine predictors of early fixation failure.Design: Retrospective cohort study.Setting: Level-one trauma center.Patients/Participants: One hundred forty-two adult patients with IT fractures treated with either a sliding hip screw (SHS) or a cephalomedullary nail (CMN) who had both pre-op plain x-ray images and CT scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…23 Again, Hecht et al showed that CT provides better and more predictable fixation results in unstable intertrochanteric femur fractures aft er preoperative use. 24 In the present study, DHS, which was preferred to apply to stable fracture patterns, was preferred in 36.20% of patients compared to x-ray, and it was preferred in 26.20% compared to x-ray/CT. We think the CT evaluation and x-ray will be less critical in the treatment of imp-lant preference in groups other than 31A1 because implant preference is for intramedullary fixation in the 31A2 and 31A3 groups with unstable fracture patterns.…”
Section: Discussionmentioning
confidence: 56%
“…23 Again, Hecht et al showed that CT provides better and more predictable fixation results in unstable intertrochanteric femur fractures aft er preoperative use. 24 In the present study, DHS, which was preferred to apply to stable fracture patterns, was preferred in 36.20% of patients compared to x-ray, and it was preferred in 26.20% compared to x-ray/CT. We think the CT evaluation and x-ray will be less critical in the treatment of imp-lant preference in groups other than 31A1 because implant preference is for intramedullary fixation in the 31A2 and 31A3 groups with unstable fracture patterns.…”
Section: Discussionmentioning
confidence: 56%
“…However, the same applies to the already established aLWT measure. Evaluating rLWT in a three-dimensional aspect from a computed tomography (CT) scan should be more accurate but would come at a higher cost and radiation exposure 23 , 24 . Today's standard in diagnosing TFF does not imply a CT scan and that is why the latter cannot be used for rLWT definition 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, postoperative burst of the lateral femoral wall is the serious complication that is thought to be the main predictor of reoperation [ 8 , 9 ]. It is because that the lateral femoral wall is crucial for maintaining the stability of intertrochanteric fractures [ 10 ]. Therefore, early and accurate detection of lateral wall burst is important.…”
Section: Introductionmentioning
confidence: 99%